Panniculitis in the newborn: a case report - Bastos,Fernando (2011)
ABSTRACT The authors present a case of panniculitis in a newborn, a rare disease in the neonatal period discussing its causes and differential diagnosis, emphasizing a possible diagnosis of erythema nodosum.